THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENGLISH LANGUAGE TEACHING: OPPORTUNITIES, CHALLENGES, AND FUTURE PERSPECTIVES - O’rozaliyeva Husniya Azimjon qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  Artificial  Intelligence  (AI)  has  emerged  as  a  transformative technology in modern education, significantly influencing the teaching and learning of foreign languages. In English Language Teaching (ELT), AI-powered tools such as intelligent  tutoring  systems,  chatbots,  speech  recognition  software,  and  adaptive learning  platforms  have  introduced  innovative  approaches  to  language  instruction. These  technologies  offer  personalized  learning  experiences,  immediate  feedback, enhanced  learner  engagement,  and  greater  accessibility  to  educational  resources. However, the integration of AI in ELT also presents challenges, including concerns regarding  academic  integrity,  data  privacy,  technological  dependence,  and  the reduction of human interaction in language learning environments. This theoretical review examines the role of AI in English language teaching through an analysis of recent scholarly literature. The study explores both the advantages and limitations of AI  applications  in  ELT  and  discusses  their  implications  for  teachers, learners,  and educational  institutions.  The  findings  indicate  that  AI  has  the  potential  to  improve language  acquisition  and  teaching  effectiveness;  however,  its  successful implementation requires a balanced approach that combines technological innovation with pedagogical principles and human-centered instruction.